Highly porous seeding-free boron-doped ultrananocrystalline diamond used as high-performance anode for electrochemical removal of carbaryl from water. (October 2022) - Vernasqui, Laís G.; dos Santos, Alexsandro J.; Fortunato, Guilherme V.; Kronka, Matheus S.; Barazorda-Ccahuana, Haruna L.; Fajardo, Ana S.; Ferreira, Neidenêi G.; Lanza, Marcos R.V.
Abstract: Boron-doped diamond (BDD) electrodes are regarded as the most promising catalytic materials that are highly efficient and suitable for application in advanced electrochemical oxidation processes targeted at the removal of recalcitrant contaminants in different water matrices. Improving the synthesis of these electrodes through the enhancement of their morphology, structure and stability has become the goal of the material scientists. The present work reports the use of an ultranano-diamond electrode with a highly porous structure (B-UNCDWS /TDNT/Ti) for the treatment of water containing carbaryl. The application of the proposed electrode at current density of 75 mA cm −2 led to the complete removal of the pollutant (carbaryl) from the synthetic medium in 30 min of electrolysis with an electric energy per order of 4.01 kWh m −3 order −1 . The results obtained from the time-course analysis of the carboxylic acids and nitrogen-based ions present in the solution showed that the concentrations of nitrogen-based ions were within the established maximum levels for human consumption. Under optimal operating conditions, the proposed electrode was successfully employed for the complete removal of carbaryl in real water. Thus, the findings of this study show that the unique, easy-to-prepare BDD-based electrode proposed in this study is a highly efficient tool which has excellent application potential for the removal of recalcitrant pollutants in water. Graphical abstract: Image 1 Highlights: Easy-to-prepare BDD-based electrode, highly efficient tool to remove recalcitrant pollutants in water. In 30 min, carbaryl was completely removed from a synthetic medium, consuming 4.01 kWh m −3 order −1 . In real water - complete CBR degradation within 20–60 min with TOC removal of 52.3–65.5%. Carboxylic acids were detected and nitrogen-based ions were within the established maximum contamination levels.